2022
DOI: 10.1186/s43093-022-00154-4
|View full text |Cite|
|
Sign up to set email alerts
|

Online sales adoption and financial resilience in Sub-Sahara Africa: the moderating role of ownership and enterprise size during Covid-19 crisis

Abstract: It is an established fact that the Covid-19 pandemic had a persistent economic uncertainty effect than health uncertainty. In this study, the researchers examined the effects of expanding sales online on the financial resilience of enterprises in sub-Sahara Africa (SSA) during the economic downturn. The researchers measured financial resilience by the extent of sales and cash-flows decline during the pandemic. The researchers collected 4751 unweighted data from the World Bank’s Enterprise Survey and it Covid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The study of [29], indicated that Information Communication Technology is a powerful tool in achieving business survivability that affects social capital building, bridging, and self-efficacy, both directly and indirectly. The entrepreneurial activity can be improved and entrepreneurs can minimize the implications of lock-downs with the help of ICT [31]. Moreover, during a pandemic, micro-entrepreneurs must think outside the box to keep their businesses afloat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of [29], indicated that Information Communication Technology is a powerful tool in achieving business survivability that affects social capital building, bridging, and self-efficacy, both directly and indirectly. The entrepreneurial activity can be improved and entrepreneurs can minimize the implications of lock-downs with the help of ICT [31]. Moreover, during a pandemic, micro-entrepreneurs must think outside the box to keep their businesses afloat.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the assisted method argues that micro(handicraft)entrepreneurs may rely on external help, such as from the government and other supply chain partners, in the event of a crisis [4]. Focusing on customers, networking with other entrepreneurs, and digitizing the business are seen as appropriate and rational tactics for micro-entrepreneurs in this study to survive during the pandemic crisis, even though the pandemic crisis has a severe impact on micro-enterprises [31]. Table 8 shows the determinants of the problems encountered by the micro-enterprises that led to business failure in terms of financial aspects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An economic shock, such as epidemic diseases (e.g., COVID), causes problems in the business environment and creates new principles and rules for buying and selling through online platforms. For example, the shock in the market can affect the supply and demand of products due to the change in the supplier sales channels [12]. Epler and Leach [11] examined salesperson bricolage during a critical sales disruption.…”
Section: Introductionmentioning
confidence: 99%
“…The correct author name is: Abass Adams. The author group has been updated above and the original article [1] has been corrected.…”
mentioning
confidence: 99%